2005
DOI: 10.2135/cropsci2003.0688
|View full text |Cite
|
Sign up to set email alerts
|

Potential Heterotic Groups in Hop as Determined by AFLP Analysis

Abstract: ␤-acid was negatively correlated among 112 female (r ϭ Ϫ0.78), and among 74 male hop genotypes (r ϭ Ϫ0.85). Hop (Humulus lupulus L.) is a perennial, dioecious species inAdditive genetic variation was detected for yield, ␣and which the female inflorescence (cones) are harvested and used in the beer-brewing process to impart bittering and/or flavoring to beer.␤-acid content, cohumulone, and hop storage index for Hop breeders have typically utilized clonal selection and hybridization both males and females in a N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
(54 reference statements)
1
8
0
Order By: Relevance
“…These genotypes are characterized by having a higher bittering acid potential and some level of powdery mildew (Podosphaera macularis Braun and Takamatus) resistance. In general, the subgroupings of A2 were similar to earlier hop characterization work based on genetic markers ( Jakse et al, 2001;Pillay and Kenny, 1996;Seefelder et al, 2000;Townsend and Henning, 2005).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…These genotypes are characterized by having a higher bittering acid potential and some level of powdery mildew (Podosphaera macularis Braun and Takamatus) resistance. In general, the subgroupings of A2 were similar to earlier hop characterization work based on genetic markers ( Jakse et al, 2001;Pillay and Kenny, 1996;Seefelder et al, 2000;Townsend and Henning, 2005).…”
Section: Resultssupporting
confidence: 78%
“…Several research groups have demonstrated the ability of various molecular marker systems to measure genetic distance among hop genotypes. Generally, genetic marker‐based assessment suggests modern hop cultivars derive from European or European × native American germplasm pools (Jakse et al, 2001; Patzak, 2002; Pillay and Kenny, 1996; Seefelder et al, 2000; Townsend and Henning, 2005). In a microsatellite analysis of 124 hop accessions from Europe, Asia, and North America, Jakse et al (2004) found that European cultivated and native hop accessions contained limited allelic variation compared to North American cultivars and native accessions.…”
mentioning
confidence: 99%
“…Thus, based on the known level of genetic variability of a population and the greatest genetic distance between the plants, the genetic gains can be quantified. For some crops these procedures have been successfully adopted, optimizing the diversity in the selected parents (Townsend and Henning 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This accession reportedly had resistance to aphids (Wagner, 1974) and for this purpose it was integrated into the USDA germplasm collection. USDA 21089M is thought to be a wild landrace from the Balkans in south‐central Europe as shown by genetic diversity studies conducted with molecular markers (Townsend and Henning, 2005). As such, little genetic similarity exists with other European landraces, such as Hallertauer, Tettnanger, or Saazer.…”
Section: Methodsmentioning
confidence: 99%